Comparison of the normal sinus node with seven types of rate responsive pacemaker during everyday activity. Issue 1 (July 1990) - Sulke, A N; Pipilis, A; Henderson, R A; Bucknall, C A; Sowton, E
Abstract : The heart rate response of 59 patients aged 17-79 years implanted with seven different types of rate responsive pacemakers was evaluated during graded exercise treadmill testing and during standardised daily activities. The heart rate response in patients with pacemakers was compared with the chronotropic response in 20 healthy controls of similar age and sex distribution who performed identical protocols. All pacemaker types adequately simulated the control heart rate response during the graded exercise treadmill test except during the early stages of exercise. However, during everyday activities, the response of ventricular rate responsive (VVIR) pacemakers was varied. Activity sensing systems rapidly overresponded to staircase descent, to changes in walking speed, and to suitcase lifting with the pacemaker arm, and these systems did not respond to mental stress. "Physiological" sensors (QT and minute ventilation units) responded slowly to rapid changes in physiological demand. The QT pacemaker patients did respond to mental stress but showed a paradoxical increase in rate during the recovery phases of burst exercise protocols such as staircase ascent/descent and walking deceleration. Dual chamber pacemakers in VDD, DDD, and DDDR modes most closely simulated the normal chronotropic response during everyday activities. Graded exercise treadmill testing, in isolation, may not be the best way to asses or program the heart rate response in patients with the heart rate adaptive pacemakers because changes in heart rate during everyday activities may deviate considerably from the normal sinus response despite satisfactory simulation of the normal chronotropic response during treadmill testing.